"At least Mom will be safe there": the role of resident safety in nursing home quality. Issue 3 (1st June 2003) - Kapp, M B
Abstract : When family members admit a loved one to a nursing home, they expect that the facility will assure the physical safety of the residents. However, this does not always occur. Safety concerns persisting in at least some modern American nursing homes involve adverse drug events, injurious falls, pressure ulcers, problems with tube feeding, faulty communications or other breakdowns during transfer to or from hospital, and equipment breakdowns or mix-ups. The adversarial legal, economic, political, and media environment surrounding the US nursing home industry poses serious practical impediments to alleviating these safety concerns more effectively. However, resident safety comprises only one part of the larger quality improvement picture in the nursing home context. While the threat of negative legal repercussions may be necessary to address safety issues, a fuller concern about improving the quality of care and quality of life for nursing home residents will also involve the development and implementation of a combination of positive incentives for facilities to do better.